UTILIZATION OF OIL PALM EMPTY FRUIT BUNCHES ENHANCED WITH MOLASSES FOR XYLITOL PRODUCTION - Clarissa, Clarissa; Valerie, Levina; Hadi, Alvinsyah Ramdani Pradipta; Purnamadjaja, Andrew Medha; Valentino, Figo; Kembaren, Riahna (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
A minimal oil palm empty fruit bunch (OPEFB) usage encourages increased OPEFB utilization to prevent its loss of economic prospects. The xylose and arabinose constituents of OPEFB’s hemicellulose part can be utilized as raw materials for xylitol production. A high diabetes mellitus and periodontal disease prevalence in Indonesia makes xylitol a safe and helpful low-calorie sweetener alternative. This research explores the OPEFB molasses-supplemented media and compares Moniliella pollinis SP5 and other M. pollinis ethyl methanesulfonate (EMS) mutants in xylitol yields. It was found that M. pollinis SP5 accomplished 27% better performance in OPEFB+15%(v/v) molasses than in OPEFB from 0.48 g/g to 0.61 g/g. In addition, M4, M5, and M6 mutants from EMS mutagenesis generated more xylitol concentration in OPEFB + 15%(v/v) molasses compared to the SP5 strain. These findings provide in-sights into the potential of xylitol manufacture with OPEFB. For future research, it is recommended that xylitol production employing OPEFB be optimized.